Perceptions of Rural Communities on Ownership and Management of Rural Water Supply Systems (RWSSS) in Lesotho and a Summary Recommendary View (Global Journal of Human-Social Science, 2015)
This is a research study that reveals some nature of the contribution of Lesotho's communities in capital and management costs and the influence of financial contributions on perceptions of ownership of rural water supply systems/RWSSs. The study is about perceptions of rural communities on ownership and management of RWSSs in Lesotho. The research further includes a summarizing recommendary view on these aspects.Research methodology encompassed semi-structured interview guides, focus group discussions and beneficiary assessment methods in Mahlabatheng, Masapong and Machache rural areas in the district of Maseru. Interviews also covered the Department of Rural Water Supply/DRWS located in Maseru city in Lesotho.
Keywords: 1 ownership of rural water supply systems; 2 rural communities; 3 rural water supply systems/rwsss; 4 management of rural water supply systems; 5